A Qualitative Exploration of Exclusive Breastfeeding Practices Among Karen Ethnicity Mothers in Northern Thailand Remote Rural Areas - Ritthimon, Wanchalerm; Thongprachum, Aksara; Wungrath, Jukkrit (UI Scholars Hub, 2023)
Low exclusive breastfeeding rates among the Karen ethnic group in Northern Thailand's remote rural areas underscore the need to understand knowledge, attitudes, and social support to develop targeted interventions. This qualitative study examined exclusive breastfeeding practices and the factors influencing breastfeeding behavior among 14 Karen Ethnicity Mothers (KEMs) in Northern Thailand. A structured interview was used to collect the data, a triangular method to determine the data's validity, and a content analysis method to examine the data revealed seven themes and 14 subthemes. This study identified three key factors for successful breastfeeding: self-motivation, social support, and effective problem management, which included overcoming the family's anti-breastfeeding beliefs. Conversely, unsuccessful breastfeeding stemmed from four issues: inadequate maternal knowledge and misconceptions, family beliefs and culture, maternal health problems, and economic constraints. Therefore, the success of breastfeeding was heavily influenced by both personal and environmental factors. As a result, every KEM should be encouraged to recognize the importance of breastfeeding and to exclusively breastfeed for at least six months, especially those living in remote rural areas and have a different way of life than the natives.